Design and analysis of wheelchair according to human factor engineering - Amir, Abdullah (2011)
The report begins with a preliminary research of human factor engineering and ergonomic study for the design of wheelchair. The main objective of this project is to concentrate the use of simulation in analyzing the critical part of the wheelchair modeling and evaluating the wheelchair design based on human factor. Evaluate the critical part of stress on the wheelchair which consists of seating support and wheel caster. In this steps, applying the knowledge gathered from the questionnaire is use to make a design refers to case data that suitable for the project. Several sketches have been made and only three have been selected based on the suitability design. Based on the sketches, material needed in this project was listed and suitable design being selected. Next the sketches being draw into SolidWorks software and then go through to simulation process by using FEA tools that is ALGOR software, the design was analyzed using constant force. Improvement of critical parts such as seating support and wheel caster design was compared based on material used, analysis on Stress Von Mises. At the end, when all the process mentioned above is done, the result for report writing is gathered. The report writing process will be guided by the Universiti Malaysia Pahang final year report writing guide.